Semi-quantitative analysis of periventricular gray-white matter ratio on CT in patients with idiopathic normal pressure hydrocephalus. (July 2022) - Sohn, GyeongMo; Bae, Min Jung; Park, Jinse; Kim, Sung Eun
Highlights: There are alterations in the periventricular gray-white matter ratio (GWR) on computed tomography (CT) in patients with idiopathic normal pressure hydrocephalus (INPH). A significant difference in the gray-white matter ratio (GWR) was found only in the anterior part of the periventricular area. The anterior part of gray-white matter ratio (GWR) on computed tomography (CT) can be used as a diagnostic tool in patients in idiopathic normal pressure hydrocephalus (INPH). Abstract: To investigate alterations in the periventricular gray-white matter ratio (GWR) on computed tomography (CT) in patients with idiopathic normal pressure hydrocephalus (INPH), a total of 140 patients with INPH and 52 age-and sex-matched controls were included by using Japanese guidelines published in 2021: possible, probable, and definite INPH for a retrospective case-control study. The non-enhanced brain CT was reviewed, and the Hounsfield unit (HU) was semi-quantitatively measured using the region of interest (ROI). The size (40 mm 2 ) and location of the ROI were standardized within the periventricular white matter (WM) and thalamus. Bilateral anterior (ant) and posterior (post) periventricular WMs were measured using the ROI. The GWR was calculated using the HU on ROI at the thalamus and ant or post-periventricular WMs: GWR = HU at thalamus/HU at periventricular WM. There was a significant difference in the GWRs between patients with INPH and controls at the group level. A significant difference in the GWRs was found only in the ant part of the periventricular area; the bilateral GWRs ant were significantly higher in patients with INPH than in controls ( p  < 0.0001 with multiple corrections). The ROC analysis clearly showed a cut-off value of GWRs (>1.17) for diagnosing INPH. The diagnostic accuracy was satisfactory: >90% with specificity and>93% with a positive predictive value. The sensitivity and negative predictive value (NPV) were acceptable: >57% with sensitivity and>50% NPV. The GWR ant on CT could be a useful and reliable diagnostic tool in patients with INPH.